WIELKOPOLSKA (GREATER POLAND) MILITARY MUSEUM: HISTORY OF AN UNUSUAL MUSEUM - Jarosław Łuczak (Index Copernicus International S.A., 2021)
The beginning of historical-military museology in Poznan dates back to the mid-19th century when the Poznan Society of Friends of Learning assumed the responsibility to save historic monuments, and began to establish the Museum of Polish and Slavic Antiquities in the Grand Duchy of Posen (Poznan). The task was to collect archival, library, and museum materials, including militaria. As a result of these efforts, in 1882, the Mielżynski Museum was established which boasted an exquisite painting gallery, containing historical painting, a rich archaeological and military collection, and a sizeable collection of so-called historical mementoes: weapons, orders, decorations, etc. In the aftermath of the Greater Poland Uprising 1918 –1919, the Hindenburg Museum founded in 1916–1918 was transformed into a Military Museum. The ceremonial opening was held on 27 October 1919 by Józef Piłsudski, Poland’s Chief of State. The quickly growing collection was moved from Marcinkowskiego Avenue to the barracks in Bukowska Street, and subsequently to a new seat at 1 Artyleryjska Street in Poznan. The solemn opening of the Wielkopolska Military Museum was held on 22 April 1923 by the Commander of the 7th Corps District Major-General Kazimierz Raszewski. In 1939, anticipating the threat of war, the most precious objects were evacuated eastwards, and looted there. The items which stayed behind ended up in German museums. The mementoes connected with the history of the Polish military were destroyed, and the Museum was wound up. The first attempts at reactivating the Museum following WW II failed. It was only with the 1956 revolt that civil and military authorities changed their approach, The National Museum in Poznan undertook the first efforts. The Museum did not go back to its pre-WW II seat, but found home in a modern building in the Old Market Square in Poznan, to be ceremoniously launched on 22 February 1963 by the Commander of the Operational Air Force in Poznan Brigadier General Pilot Jan Raczkowski. Having recreated its collection, the Wielkopolska Military Museum, already as a Branch of the National Museum in Poznan, has held many exhibitions and shows. Moreover, it has released many publications, and run a broad range of educational activities. Among other projects, it has also made reference to the pre-WW II Museum. On 27 December 2019, a new jubilee exhibition ‘Wielkopolska Military Museum 1919–2019’ recording the 100-years’ history of the oldest historical-military museum in Poland was inaugurated.